ECONOMY OF MATERIAL AND ENERGY RESOURCES AT THERMAL TREATMENT - A. I. Garost (Литьë и металлургия, 2009)
The article offers ecologically harmless heat treatment method  for pieces made of black metals. It can override import methods.  The water polymer solutions are used like cooling fluid. The traditional heat treatment methods (like cooling in water or oil) and new method are compared in the article. The criterions of cooling can be established by changing solution concentration for different steels. Using the method of electronic scanning microscopy  we have studied structure and micro composition of films formed on a heat treated surface.